Developing Spinning Wheel as an Assessment Media in Speaking - Yuka Hutami; Wiyanah, Sri (Universitas PGRI Yogyakarta, 2024)
This research endeavors to confront the impediments in teaching English speaking skills to junior high school students in Indonesia. It acknowledges the prevalent skepticism and monotony linked with conventional language learning approaches. To address this, the study introduces the Spinning Wheel, an inventive assessment tool designed to invigorate student engagement in English speaking. Employing a Research and Development (R&D) strategy and the ADDIE model by Dick and Carey, the study focuses on 8th-grade students at SMPN 2 Sentolo. Validation from teachers, material experts, and media experts serves as the research instrument. The Spinning Wheel is systematically developed and integrated into the classroom to create a more enjoyable and effective learning experience. Evaluation indicates positive outcomes, demonstrating heightened student interest and confidence in speaking English. The findings suggest that incorporating innovative assessment media, like the Spinning Wheel, positively influences language learning. The research starts with an in-depth Analysis, identifying the specific needs of eighth-grade students in speaking skills. The subsequent Design phase shapes the Spinning Wheel Assessment Media, aligning it with curriculum goals. Development ensures pedagogical soundness, and Implementation brings the tool to life for 32 students in an engaging environment. The Evaluation phase gauges the media's efficacy, with teacher, material expert, and media expert assessments categorizing it as